Pengaruh Pemanasan Terhadap Kualitas Minyak Goreng Dengan Metode Polarisasi Cahaya - Rahayu, Ratna Dwi (SIMETRIS, 2025)
The use of cooking oil for too long and repeatedly will cause changes in color, odor, and physical and chemical properties of the cooking oil itself. However, the public generally lacks knowledge and awareness about the quality of good cooking oil to use. As an alternative, research has been conducted on testing the quality of cooking oil based on changes in the angle of polarization of light using a polarimeter. The cooking oil to be tested was previously heated to a temperature of 100 degrees Celsius with a variation of five heating times. The results of the polarization angle change test showed that the cooking oil without heating had the smallest polarization angle of 0.2 degrees, then with five heating times the polarization angle increased to 10.9 degrees. This indicates a change in the physical properties of cooking oil that has not been heated with cooking oil that has been heated repeatedly.